Temperature‐dependent transport and photoelectric properties in La0.9Hf0.1MnO3 based all‐perovskite‐oxide heterojunctions. Issue 10 (11th June 2014) - Wang, L.; Wu, Z. P.; Jiang, Y. C.; Ren, B.; Huang, J.; Tang, K.; Zhang, J. J.; Gao, J.; Wang, L. J.
Abstract : All‐perovskite‐oxide heterojunctions composed with tetravalent cation‐doped La0.9 Hf0.1 MnO3 (LHMO) and 0.7 wt% Nb‐doped SrTiO3 were fabricated using pulsed laser deposition method. Compared to those hole‐doped manganites‐based junctions, much stronger rectifying characteristics were observed in the formed junctions. Special attention has been paid to the temperature dependence of photovoltage ( V oc ) and short‐circuits current ( I sc ). It is notable that, under illumination of a light with λ = 532 nm, the V oc dropped from 700 to 120 mV as the temperature increasing. No sudden change of V oc was observed in the whole temperature from 40 to 300 K. However, a maximum of the short‐circuit current was found near the ferromagnetic to paramagnetic phase transition temperature. The energy band diagram of such heterojunctions is constructed and physics related to the rectifying behaviors and photoelectric effect is discussed.